Economics and Value Judgments - Streeten, Paul (Quarterly Journal of Economics, 1950)
Introduction, 583. — I. The neutrality of means, 585. — II. The value of individual choice, 588. — III. Interpersonal comparisons, 591. — IV. The criterion for an "improvement, " 593. — V. Conclusions, 594.